2002
DOI: 10.1109/tsmcb.2002.1018769
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamic system identification using Chebyshev functional link artificial neural networks

Abstract: A computationally efficient artificial neural network (ANN) for the purpose of dynamic nonlinear system identification is proposed. The major drawback of feedforward neural networks, such as multilayer perceptrons (MLPs) trained with the backpropagation (BP) algorithm, is that they require a large amount of computation for learning. We propose a single-layer functional-link ANN (FLANN) in which the need for a hidden layer is eliminated by expanding the input pattern by Chebyshev polynomials. The novelty of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
122
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(125 citation statements)
references
References 31 publications
0
122
0
3
Order By: Relevance
“…Functional Link Neural Network is a class of HONNs created by Pao [7] and has been successfully used in many applications such as system identification [9][10][11][12][13][14], channel equalization [3], classification [15][16][17][18], pattern recognition [19,20] and prediction [21,22]. In this paper, we would discuss on the FLNN for the prediction task.…”
Section: Functional Link Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional Link Neural Network is a class of HONNs created by Pao [7] and has been successfully used in many applications such as system identification [9][10][11][12][13][14], channel equalization [3], classification [15][16][17][18], pattern recognition [19,20] and prediction [21,22]. In this paper, we would discuss on the FLNN for the prediction task.…”
Section: Functional Link Neural Networkmentioning
confidence: 99%
“…This model uses a tensor representation. Pao [7], Patra [10], Namatamee [24] has demonstrated that this architecture is very effective for classification task. …”
Section: Functional Link Neural Networkmentioning
confidence: 99%
“…Combining the characteristics of the FLNN and Chebyshev orthogonal polynomial resulted in a new FLNN named Chebyshev FLNN (CFLNN) [105,106,124]. The basic principles of this method is same as previously discussed model, but the basis function considered here are Chebyshev polynomials.…”
Section: Functional Link Neural Network With Chebyshev Polynomialmentioning
confidence: 99%
“…A Chebyshev functional link artificial neural networks (CFLNN) has proposed by Patra et al [106] for non-linear dynamic system identification. This is obviously another improvement in this direction and also a source of inspiration to further validate this method in other application domain.…”
Section: Functional Link Neural Network: a Road Mapmentioning
confidence: 99%
“…Simulation results showed that the performance identification using neural MIMO NARX model trained by back-propagation algorithm performed well. However, the drawback of the backpropagation algorithm applied in the studies [4], [5], [6] and [7] was that the convergence speed became slow, a large computation for learning and the cost function might lead to local minima.…”
Section: Introductionmentioning
confidence: 99%